Law Enforcement Against Perpetrators Participating in Corruption Crimes in Higher Education Institutions in Indonesia - Febrianto, Febrianto (Dinasti Research, 2024)
The purpose of this study is to examine how law enforcement applies to perpetrators who participate (medepleger) in criminal acts of corruption. This study uses a normative juridical legal research method with a case approach in the Tanjungkarang District Court Decision Number 1/Pid.Sus-TPK/ 2023/PN.Tjk and analyzed using evaluative methods. The results of the study conclude that law enforcement against criminal acts of corruption carried out jointly must be carried out fairly and effectively, taking into account the unity of intention and cooperation between the perpetrators. It is hoped that the results of this analysis can contribute to the development of criminal law studies, especially in handling corruption cases involving many parties.